Die Entwicklung der Matriarchatsdebatte im deutschsprachigen Raum - Maged-Scherney, Ingrid (Österreichische Zeitschrift für Geschichtswissenschaften, 1995)
The paper first analyzes the importance of the debate on matriarchy as a paradigm for the constitution of the new women's movement directed against a range of patriarchally determined theories and against the patriarchal social conditions. The search for identification and the development of feminist theories were based on historical matriarchy; this is shown by means of a synthesis of older works by Bachofen, Vaerting and Eckstein-Diener and new approaches such as those of Bornemann and Göttner-Abendroth. A critical reception is included, exploring the projections into the past within the concepts of matriarchy and the discussion on godesses which influence spiritualism as well as esoterics. In the article, the present-day context is particularly considered by the development of feminist ethnology which sheds new light on the debate on matriarchal societies and on the gender-specific suppression of females in the Third World. The paper concludes that the term matriarchate(s) intended to oppose against the androcentric claim and that continuing the discussion guarantees that research on women will be carried on.